Clinical Repercussions of Guillain-Barré Syndrome: A Case Study and Systematic Review - Souza, Lígia Maria Oliveira de; Vigilato , Paloma Marcela; Bellizzi, Alessandra Savi; Jayder Braga Alencar, Dalle; Costa, Gustavo Mendes Rezende; Gomez, Andrea Paola Britos; Souza, Bárbara Priscila Alves de; Segovia, José Andrés Alfonzo (Brazilian Journal of Case Reports, 2025)
Guillain-Barré Syndrome (GBS) is part of a heterogeneous group of immune-mediated polyneuropathies characterized by segmental demyelination accompanied by mononuclear infiltrates in the endoneural tissue and myelin sheaths. It is a rare neurological disorder that primarily affects adults. Its origin is often post-infectious, triggered by an autoimmune response against the peripheral nervous system, which leads to the classic triad: paresthesia, progressive and ascending muscle weakness with areflexia, and, in severe cases, paralysis. Its onset is related to previous infections, often caused by Campylobacter jejuni, cytomegalovirus, or the Epstein-Barr virus. The diagnosis is generally straightforward and is determined through a complete medical history, a neurological examination focusing on identifying the triad, and complementary tests such as electromyography and cerebrospinal fluid analysis. Within days, the cerebrospinal fluid often shows elevated protein levels, while the cellular content remains largely unchanged, resulting in albuminocytologic dissociation. Treatment includes respiratory support in severe cases, intravenous immunoglobulin, or plasmapheresis. Recovery depends on several factors and may take weeks or even months. This study presents the case of a 46-year-old man who developed GBS following a prior infection. The case highlights the diagnostic challenges, clinical progression, and the implementation of treatment. Its onset is related to previous infections, often caused by Campylobacter jejuni, cytomegalovirus, or the Epstein-Barr virus. The diagnosis is generally straightforward and is determined through a complete medical history, a neurological examination focusing on identifying the triad, and complementary tests such as electromyography and cerebrospinal fluid analysis. Within days, the cerebrospinal fluid often shows elevated protein levels, while the cellular content remains largely unchanged, resulting in albuminocytologic dissociation. Treatment includes respiratory support in severe cases, intravenous immunoglobulin, or plasmapheresis. Recovery depends on several factors and may take weeks or even months. This study presents the case of a 46-year-old man who developed GBS following a prior infection. The case highlights the diagnostic challenges, clinical progression, and the implementation of treatment.